Political change in Southeast Asia : trimming the banyan tree - Vatikiotis, Michael R. J., 1957- (Routledge, 1996)
Recovering tradition. Deus ex impera. Differing on democracy. Core values or elitist cores. The religious challenge to authority. Coming toghether.